A Drug‐Free, Hair Follicle Cycling Regulatable, Separable, Antibacterial Microneedle Patch for Hair Regeneration Therapy. Issue 19 (29th July 2022) - Shi, Yan; Zhao, Jiaxuan; Li, Hu; Yu, Miao; Zhang, Wenxue; Qin, Di; Qiu, Kaijin; Chen, Xiguang; Kong, Ming
Abstract: The development of painless hair loss therapy without side‐effect is challenging. The dermal papilla is the signal center of hair follicles and plays a key role in the regulation of their cycling. Activation of dermal papilla cells (DPCs) would promote hair regeneration. In this study, a separable microneedle patch comprised of chitosan lactate (CL) and exosomes (EXO) from adipose‐derived stem cells is fabricated. After insertion of the microneedle into the skin, the hyaluronic acid substrate dissolves fast and the swellable polyvinyl alcohol needles are retained. The EXO sustainedly released from needles can be endocytosed by DPCs and promote cell proliferation via the activation of the Wnt signaling pathway, while the L‐lactate released by CL can promote cell growth by activating lactate dehydrogenase. CL and EXO synergetically facilitate hair regeneration through regulating hair follicle cycling. In animal tests, compared with topical administration of minoxidil, the drug‐free microneedle patches can more significantly promote hair regeneration within 7 days with lower dosing frequency. Furthermore, the inherent antibacterial properties of CL make it possible to avoid potential infection. Such transdermally administrated drug‐free microneedle patches provide a simple, safe, and efficient strategy for hair loss treatment and exhibit great potential in clinical application. Abstract : A drug‐free separable microneedle for hair regeneration is prepared, the needles of which contained exosomes extracted from adipose derived stem cells and chitosan lactate. After being inserted into the skin, the hyaluronic acid substrate is rapidly dissolved, leaving the polyvinyl alcohol needles in the skin to release exosomes and L‐lactate, thereby regulating the hair follicle cycling and promoting hair regeneration.